TRP channels in gastric cancer: New hopes and clinical perspectives. (September 2019) - Sterea, Andra M.; Egom, Emmanuel E.; El Hiani, Yassine
Graphical abstract: Graphical Abstract: Schematic depiction of the current and emerging therapies for gastric cancer patients. Surgery has long been the therapy of choice for gastric cancer patients (or any cancer type), in particular those with localized tumors and earlier stages of the disease. However, patients with late stage are often treated with chemotherapy, radiation or a combination of surgery, chemotherapy or radiation. Although successful to a certain extent, these approaches are not always curative and achieve varying clinical outcomes which are largely attributed to tumor heterogeneity. It is these challenges that led to the development of new therapies. Emerging cancer therapies are moving towards personalized medicine where each patient is treated according to their tumor expression profile and genetic makeup. These new therapy options include immunotherapy and targeted therapy which have shown good efficacy at treating gastric cancer patients, but various limitations still pose a significant strain on their effectiveness. Studies are now being conducted to assess the involvement of ion channels in the pathophysiology of gastric cancer in efforts of improving the efficacy of cancer treatment. Thus far, the TRP ion channel family (shown at the head of the arrow) has been demonstrated to play significant roles in gastric cancer cell survival and are currently under investigation as potential therapeutic targets for gastric cancer patients. Highlights: Gastric cancer remains one of the leading causes of cancer death for both men and women worldwide. Stomach resection is the only therapeutic option, but not always possible. Targeted therapies present new therapeutic approaches. Targeting TRP channels may represent the tipping point to kill gastric cancer. Abstract: Gastric cancer is a multifactorial disease associated with a combination of and environmental factors. Each year, one million new gastric cancer cases are diagnosed worldwide and two-thirds end up losing the battle with this devastating disease. Currently, surgery represents the only effective treatment option for patients with early stage tumors. However, the asymptomatic phenotype of this disease during the early stages poses as a significant limiting factor to diagnosis and often renders treatments ineffective. To address these issues, scientists are focusing on personalized medicine and discovering new ways to treat cancer patients. Emerging therapeutic options include the transient receptor potential (TRP) channels. Since their discovery, TRP channels have been shown to contribute significantly to the pathophysiology of various cancers, including gastric cancer. This review will summarize the current knowledge about gastric cancer and provide a synopsis of recent advancements on the role and involvement of TRP channels in gastric cancer as well as a discussion of the benefits of targeting TPR channel in the clinical management of gastric cancer.